Kritik Fenomenologis Merleau-Ponty atas Filsafat Pengetahuan - Mukhtasar Syamsuddin (Universitas Darussalam Gontor, 2010)
The main purpose of this article consists in investigating the phenomenological perspective used by Merleau-Ponty in evaluating critically the conception of knowledge. This investigation is aimed at finding a new path for understanding the essence of knowledge that is formulated by some philosophical mainstreams, such as naturalism and objectivism. Ponty’s phenomenological critique to the philosophy of knowledge is related to to the description of knowledge as a human condition, which makes the thinking of the knowledge problem possible. The phenomenological account that Ponty offers is that we experience ourselves, not as distinct ‘minds’ and ‘bodies’, but as unified persons who form intentions and act in the world, but can do so only because our bodies function mechanically in certain ways. As being poured in his work “the Structure of Behavior”, Ponty explained that the integration of matter, life and mind are obtained by reduction to a common denominator of physical form. This explanation emphasized that the Gestalists had misunderstood the ultimate implications of their own work, because they believed that the notion of structure can be thought within the naturalist ontology that subtended the thought of the atomists whom they had criticized.